2019
DOI: 10.1007/s00520-019-05037-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient co-payments for women diagnosed with breast cancer in Australia

Abstract: Purpose Among Australian women, breast cancer is the most commonly diagnosed cancer. The out-of-pocket cost to the patient is substantial. This study estimates the total patient co-payments for Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme (PBS) for women diagnosed with breast cancer and determined the distribution of these costs by Indigenous status, remoteness, and socioeconomic status. Methods Data on women diagnosed with breast cancer in Queensland between 01 July 2011 and 30 June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The average out-of-pocket costs and number of MBS services and PBS prescriptions claimed were similar to a study looking at these factors over three years post diagnosis [ 17 ]. Of interest here is that the average cost to the individual, and average number of services claimed, remained steady over a five-year period after the initial six months post diagnosis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The average out-of-pocket costs and number of MBS services and PBS prescriptions claimed were similar to a study looking at these factors over three years post diagnosis [ 17 ]. Of interest here is that the average cost to the individual, and average number of services claimed, remained steady over a five-year period after the initial six months post diagnosis.…”
Section: Discussionsupporting
confidence: 66%
“…A study by Gordon et al found that the median out-of-pocket costs for women with breast cancer was AU$4192 in the first two years post-diagnosis [ 16 ]. Another study indicated that average co-payments for MBS items in the first three years following a breast cancer diagnosis was AU$1400 (SD = $1946), while average co-payments for pharmaceuticals was $AU974 (SD = $707) in the same period [ 17 ]. While providing an indication of the out-of-pocket costs for breast cancer for Australian women, the long-term out-of-pocket costs (costs incurred over five or more years) resulting from a breast cancer diagnosis have yet not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, [25] found that among 235,368 French patients diagnosed with early breast cancer between 2011 and 2017 (identified by the Oncology Data Platform -(ODP) of the French National Cancer Institute (INCa)), 95% were 40 years old or above at the time of diagnosis. [29] used the Queensland Cancer Registry and found that among 3,079 women diagnosed with breast cancer in Queensland (Australia) between July 1st 2011 and June 30th 2012, 87.9% were older than 45 years. Based on our findings and the above-mentioned reports from the literature, it could be assumed that most women diagnosed with breast cancer are over 40 years of age.…”
Section: Discussionmentioning
confidence: 99%